Team-Based Learning of Evidence-Based Medicine: Screening - Joan M. Bedinghaus; David Nelson (Association of American Medical Colleges, 2013)
Abstract Introduction This team-based learning session is one of a series of five developed for a course called "Foundations of Evidence-Based Medicine" for first-year medical students. Of these five, four are published on MedEdPORTAL and cover the topics of randomized controlled trials, case-control and cohort studies, diagnostic testing, and screening. Methods The resource includes a list of objectives, preparation assignments, slides for a brief in-class presentation, a quiz, and application exercises. An instructor's manual is also included. Students arrive at the session having already reviewed a series of preparatory readings. They are first administered an individual readiness assurance test before being grouped into teams of 5-7 students and retake the same test (group readiness assurance test) as a unit. This is followed by a review of the answers and an informational PowerPoint presentation. Finally, the students complete a series of application exercises while remaining in their groups. Results The course was given twice (Fall 2011 and Spring 2012), each time with a group of 100-104 students. Discussion Previously, we had taught evidence-based medicine using 10-12 hours of lecture, three 1.5 hour small group sessions, and two online self-study modules. The course was poorly rated by students and the performance on USMLE in biostats was consistently below national averages. The sessions published here were developed in hopes of improving understanding and retention of evidence-based medicine concepts.